ANALISIS PENGARUH DEWAN KOMISARIS, DANA SYIRKAH DAN KONTRIBUSI SOSIAL TERHADAP KINERJA BANK UMUM SYARIAH DI INDONESIA - Gandhi Agung Wibowo; Adityawarman Adityawarman (Diponegoro Journal of Accounting, 2017)
The purpose of this research is to examine the relationship between board size, board composition, investment account holders and social contribution with the bank performance in one of the fastest-growing industries, Islamic banking. The study was conducted at nine Islamic banks exist in Indonesia. Multiple regression was used to investigate such relationship applying data from 54 sample in Indonesian over the period of 2010 until 2015. The results show that board size has negative significant on bank performance. On the other hand, composition of the board has insignificant effect. Investment Account Holders has positif significant and social contribution (zakah) has insignificant effect on bank performance. As for the control variable, bank size has significant effect on bank performance.